2022
DOI: 10.1371/journal.pone.0262323
|View full text |Cite
|
Sign up to set email alerts
|

Do empowered women receive better quality antenatal care in Pakistan? An analysis of demographic and health survey data

Abstract: Introduction Quality antenatal care is a window of opportunity for improving maternal and neonatal outcomes. Numerous studies have shown a positive effect of women empowerment on improved coverage of maternal and reproductive health services, including antenatal care (ANC). However, there is scarce evidence on the association between women’s empowerment and improved ANC services both in terms of coverage and quality. Addressing this gap, this paper examines the relationship between multi-dimensional measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
(36 reference statements)
3
19
0
Order By: Relevance
“…The results indicated higher access among those with higher education and income, those with managerial positions, those who can make a decision concerning their health care, mobility, and income, and those who are against wife-beating; however, the authors ignored the confounding effect of household's wealth index-which we did-in examing the effect of different women empowerment indicators on adequate ANC and yet reported it as an independent variable in uencing the access to ANC (22). Similar ndings were observed in Asim et al's study (23); however; the authors used the SWPER index which is to some degree similar to our index but developed based on pooled data from several countries in different regions around the globe and includes some indicators such as frequency of reading newspaper, age difference, and education difference that appeared as poor predictors of women empowerment in our study; meanwhile, it failed to take into account the women participation in the labor market which was the strongest predictor of women empowerment in our study (20), and emphasize the importance of a country-speci c scale. Another study by Hou and Ma supported the positive effect of women's decision-making on the utilization of reproductive and maternity care services using the data from Pakistan Social and Living Standards Measurement Survey, yet not addressed the impact of other domains of women empowerment that emerged in our study (21).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results indicated higher access among those with higher education and income, those with managerial positions, those who can make a decision concerning their health care, mobility, and income, and those who are against wife-beating; however, the authors ignored the confounding effect of household's wealth index-which we did-in examing the effect of different women empowerment indicators on adequate ANC and yet reported it as an independent variable in uencing the access to ANC (22). Similar ndings were observed in Asim et al's study (23); however; the authors used the SWPER index which is to some degree similar to our index but developed based on pooled data from several countries in different regions around the globe and includes some indicators such as frequency of reading newspaper, age difference, and education difference that appeared as poor predictors of women empowerment in our study; meanwhile, it failed to take into account the women participation in the labor market which was the strongest predictor of women empowerment in our study (20), and emphasize the importance of a country-speci c scale. Another study by Hou and Ma supported the positive effect of women's decision-making on the utilization of reproductive and maternity care services using the data from Pakistan Social and Living Standards Measurement Survey, yet not addressed the impact of other domains of women empowerment that emerged in our study (21).…”
Section: Discussionsupporting
confidence: 92%
“…The original index was designed to measure women's empowerment in Afghanistan including seven domains; namely, labor force participation, attitude toward violence, decision-making, access to healthcare, literacy, age at critical life events, and property-owning; however, our analysis showed that the 6-factor model-excluding the property-owning-could better explain the woman empowerment among married women aged 15-49 years in Pakistan with an acceptable internal consistency (Cronbach's α = 0.70) and construct validity (SRSEA&SRMR < 0.05, CFI&TLI > 0.95). Moreover, to estimate the convergence validity of the developed index, we selected four indicators of access to reproductive and maternity care including the unmet need for family planning, adequate ANC, institutional delivery, and skilled birth attendance that have shown to be strongly associated with high women empowerment (9,19,20,23,42) and examine their associations with emerged domains. All six domains appeared to be strongly associated with at least one favorable outcome; indicative of a decent convergence validity of the 6-factor model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Working women had lower odds of receiving all ANC components. This is contrary to the evidence that women who work have higher prospects of effective maternal healthcare utilisation because they are likely to have a wider social network and receive information from other women they meet at the work place [ 6 , 54 , 55 ]. This may present an opportunity for them to learn about quality ANC and its importance and hence demand for it during ANC visits, unlike those who do not work.…”
Section: Discussionmentioning
confidence: 63%